(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
In this study, composite briquettes were produced from agricultural waste (rice husks and palm kernel shells) using a manually operated 20-ton air hydraulic press fabricated for this purpose. This research addresses current fuel sources’ environmental and economic challenges by developing an alternative solid fuel from agricultural waste. The rice husk and palm kernel shell samples were ground into powder and sieved with a 1 mm sieve mesh. Thereafter, (RH) and (PKS) samples were thoroughly mixed to obtain a uniform and homogeneous mixture. The mixtures were prepared at RH: PKS weight ratios of 90:10, 80:20, 70:30, 60:40, 50:50, 100:0, and 0:100 and compacted under a pressure of 110 bar using 25% gelatinized starch as a binder. The experimental results of the produced briquettes showed that the compressed and relaxed densities of the fuel briquettes ranged from 0.84 to 1.09 g/cm³ and 0.54 to 0.68 g/cm³, respectively. Proximate analysis of the briquettes showed that the percentages of moisture, ash, volatile matter, and fixed carbon ranged from 4.18 to 5.57%, 12.48 to 19.32%, 74.39 to 81.38%, and 0.05 to 2.11%, respectively. The results for higher heating value (HHV) ranged from 16.92 to 19.19 MJ/kg, which compared well with the standards of the American Society for Testing and Materials (ASTM). The briquette with a 50RH:50PKS ratio recorded the highest HHV of 19.19 MJ/kg, implying it has a higher heating advantage over the remaining samples and is therefore recommended as an alternative fuel to conventional fuels (charcoal and firewood).